2015
DOI: 10.1016/j.jval.2015.09.1193
|View full text |Cite
|
Sign up to set email alerts
|

Adding Bevacizumab To Single-Agent Chemotherapy For The Treatment Of Platinum-Resistant Recurrent Ovarian Cancer: A Cost-Effectiveness Analysis Of The Aurelia Trial

Abstract: These results include women of any age and mammography of any type. ConClusions: Results suggest that annual mammography is mostly cost-effective when compared to no screening. According to a $100,000/QALY threshold, most of analyzed studies suggest that combined screening is costeffective in high-risk women compared to mammography alone, despite a wide cost-effectiveness ratios range. Notwithstanding the high level of heterogeneity among selected studies, this review provides a comprehensive overview of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Using the results of the AURELIA trial, a conference abstract was recently published in which a decision-tree-based cost-effectiveness analysis was undertaken from a US public payer perspective [ 20 ]. This study reported an ICER of $US285,624 per QALY gained over a 15-month time horizon.…”
Section: Discussionmentioning
confidence: 99%
“…Using the results of the AURELIA trial, a conference abstract was recently published in which a decision-tree-based cost-effectiveness analysis was undertaken from a US public payer perspective [ 20 ]. This study reported an ICER of $US285,624 per QALY gained over a 15-month time horizon.…”
Section: Discussionmentioning
confidence: 99%